Energy Policy Making in the EU: Building the Agenda - Tosun, Jale (Springer, 2016)
The book adopts an innovative analytical approach to agenda setting by not only presenting successful cases in which energy issues were addressed by means of public policy, but by also analyzing failed attempts to make issues part of the European policy agenda. Another outstanding feature of the book is its use of the latest empirical data on a broad range of energy issues.